1997
DOI: 10.1007/s002800050708
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of metallothionein content and subcellular localization in the National Cancer Institute tumor panel

Abstract: These results demonstrated significant diversity in MT content and subcellular localization in human tumor cells. Moreover, both basal MT levels and subcellular distribution appeared to be determinants of cellular responsiveness to metal-containing compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…The potential for basal levels of endogenous (e.g., oxidative) stress, associated with abnormal zinc availability (14), to exert any cell cycle disturbing effects will depend not only on the availability of protective mechanisms for a given type of stress, but also on the ability of the cellular system to enact a cell cycle-linked response. In general, it appears that cytoplasmic MT protects against cytotoxicity, whereas nuclear MT protects against genotoxicity (1,2,8,40,57,58). Our distribution study indicated a primarily cytoplasmic location for enforced MT-1 overexpression.…”
Section: Discussionmentioning
confidence: 48%
“…The potential for basal levels of endogenous (e.g., oxidative) stress, associated with abnormal zinc availability (14), to exert any cell cycle disturbing effects will depend not only on the availability of protective mechanisms for a given type of stress, but also on the ability of the cellular system to enact a cell cycle-linked response. In general, it appears that cytoplasmic MT protects against cytotoxicity, whereas nuclear MT protects against genotoxicity (1,2,8,40,57,58). Our distribution study indicated a primarily cytoplasmic location for enforced MT-1 overexpression.…”
Section: Discussionmentioning
confidence: 48%
“…Likewise, MT levels were also significantly increased in patients not responding to cisplatin and carboplatin treatment [79]. Moreover, in cultures of malignat cells MT levels are often significantly increased resulting in an even stronger Pt II scavenging effect [77,[80][81][82]. MT expression during cancer development was addressed for various malignant cells and tissues [83] where the degree of MT expression and the influence on cancer development showed a strong diversity among the investigated types of tissue and cells [81,84].…”
Section: Metallothionein and Platinum Treatmentmentioning
confidence: 99%
“…Thus, in the same cell line, physiological changes of the glutathione redox potential affect the redox state of MT and the amount of "free" zinc, clearly linking the availability of zinc, MT, and redox metabolism. Many factors induce MT expression and thereby alter the zinc and redox buffering capacity; the protein varies at least 400-fold in different cell lines (23). The protein that is induced, however, is thionein, not metallothionein.…”
Section: Cellular Zinc Buffering Capacity and "Free" Zincmentioning
confidence: 99%